Penjaminan Keberlanjutan Pembangunan Kapal Kayu Melalui Pelatihan Pembuatan Pola Gading untuk Penerapan Inovasi Gading Baja Sebagai Pengganti Gading Kayu bagi Pengrajin Kapal Kayu di Kabupaten Takalar - Mohammad Rizal Firmansyah; Lukman Bochary; Syamsul Asri; Muhammad Rusydi Alwi; Misliah Idrus; Ganding Sitepu; Wihdat Djafar; Rosmani - (Faculty of Engineering UNHAS, 2019)
Currently wood raw material used for ivory or wooden ship frames is increasingly difficult to obtain because it has a special shape, where the wood for the ship's ivory must be taken from the tree in the form of curved beams, so that it is easily shaped according to the shape of the wooden ship that will be built. Some wooden ship craftsmen in South Sulawesi have faced this difficulty. One of them is a wooden ship craftsman who is part of a group of wooden ship craftsmen